Abortion and Women’s Bodily and Mental Health: the Language of Trauma in the Public Debate on Abortion in Italy - Claudia Mattalucci (Antropologia, 2018)
In this paper, I analyse the political use of the notion of trauma in the public debate on abortion in Italy. Its genealogy can be traced back on the one hand to the feminism of the 1970s, when abortion was illegal and unsafe, and on the other to the scientific debate initiated in the United States during the 1980s, relating to the effects of legal and safe abortion on women’s mental health. During the early 2000s, the contentious diagnostic category of Post-Abortion Syndrome entered the public debate in Italy, becoming a core topic of anti-abortion activism. The idea of abortion being a trauma, however, is a view shared not only by those who protest against the law authorizing voluntary termination of pregnancy, but also by those who campaign to guarantee its application. In the context of different regulatory frameworks and moral worlds, the notion of trauma conveys different situated ideas of health and of choice.